Epidemiology of Contact Dermatitis and Contact Allergy - Uter, Wolfgang; Diepgen, Thomas L. (Springer International Publishing, 2020)
Contact dermatitis and contact allergy are common medical conditions. But how common are they? Are certain populations, e.g., certain occupations, more affected than others? Are reactions to specific contact allergens more prevalent than to other allergens or more common in a particular subgroup? This chapter presents some basic epidemiologic principles which are important in population-based or clinic-based studies on contact dermatitis. The chapter deals with methodological issues in the analysis of clinical epidemiological studies, i.e., among patients undergoing patch testing. Common pitfalls are addressed, and factors important for the occurrence of contact dermatitis and/or contact allergy are discussed. Examples of studies on contact allergy as well as contact dermatitis in general are presented.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Contact allergy; Contact dermatitis; Epidemiology; Incidence; Occupational contact dermatitis; Patch testing; Prevalence; Questionnaire